2011
DOI: 10.1002/gcc.20886
|View full text |Cite
|
Sign up to set email alerts
|

A novel WWTR1‐CAMTA1 gene fusion is a consistent abnormality in epithelioid hemangioendothelioma of different anatomic sites

Abstract: The classification of epithelioid vascular tumors remains challenging, as there is considerable morphologic overlap between tumor subtypes, across the spectrum from benign to malignant categories. A t(1;3)(p36.3;q25) translocation was reported in two cases of epithelioid hemangioendothelioma (EHE), however, no follow-up studies have been performed to identify the gene fusion or to assess its prevalence in a larger cohort of patients. We undertook a systematic molecular analysis of 17 EHE, characterized by clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
321
3
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 464 publications
(337 citation statements)
references
References 43 publications
7
321
3
6
Order By: Relevance
“…7 Ten years later, two back-toback studies, using different methodologies, were able to clone the genes involved in the t(1;3)(p36.3;q25) translocation. 8,9 WWTR1 (also called TAZ), on 3q25, is a gene involved in 14-3-3 transcriptional factor activation and signaling in the hippo pathway that is normally highly expressed in endothelial cells. 10 WWTR1 fuses to CAMTA1, on 1p36, which belongs to a family of calmodulinbinding transcription activators, normally found only in brain.…”
Section: Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Ten years later, two back-toback studies, using different methodologies, were able to clone the genes involved in the t(1;3)(p36.3;q25) translocation. 8,9 WWTR1 (also called TAZ), on 3q25, is a gene involved in 14-3-3 transcriptional factor activation and signaling in the hippo pathway that is normally highly expressed in endothelial cells. 10 WWTR1 fuses to CAMTA1, on 1p36, which belongs to a family of calmodulinbinding transcription activators, normally found only in brain.…”
Section: Geneticsmentioning
confidence: 99%
“…The 1p36 region is frequently lost in neuroblastoma and gliomas, implicating CAMTA1 as a tumor suppressor gene. 11,12 Most cases with classic morphology (ie, lacking mature vascular channel formation) examined so far contain this translocation, 8,9 which is not directly targetable with present day therapeutics, but may reveal downstream targets in future studies.…”
Section: Geneticsmentioning
confidence: 99%
“…Immunohistochemically, these tumors are positive for cytokeratin (especially CK18), and vascular markers including CD31, factor VIII-antigen, ERG and FLI-1. Recent studies have described a recurrent genetic fusion WWTR1-CAMTA1 in EHE [13], involving t(1;3) (p36;q25). This results in a reciprocal chromosomal translocation involving a fusion of the promoter of the WWTR1 gene with the carboxyl terminus CAMTA1 gene.…”
Section: Histologymentioning
confidence: 99%
“…This results in a reciprocal chromosomal translocation involving a fusion of the promoter of the WWTR1 gene with the carboxyl terminus CAMTA1 gene. These have not been seen in other vascular tumors and, hence, some authors have suggested that it could be used in difficult cases to distinguish EHE from its morphological mimics [13,14]. YAP1-TFE3 gene fusions have been identified in a subset of EHEs where WWTR1-CAMTA1 fusion was not identified [15].…”
Section: Histologymentioning
confidence: 99%
“…Beyond morphologic assessment, EHE can be distinguished from other benign and malignant vascular lesions (including epithelioid angiosarcoma) by detection of the WWTR1-CAMTA1 gene fusion by either FISH or PCR-based methods. The use of a novel immunohistochemical stain for CAMTA1 has recently been studied (9,23,24).…”
mentioning
confidence: 99%